Identification and expression of the gap segmentation gene hunchback in Drosophila melanogaster. - Bender, M.; Horikami, S.; Cribbs, D.; Kaufman, T.C. (Developmental Genetics, 1988)
Genetic analysis has shown that the gap segmentation gene hunchback (hb) is a member of the genetic hierarchy involved in pattern formation in Drosophila. To identify the hb gene, we have mapped the position of hb mutant breakpoints within a chromosomal walk of the 85A region by genomic Southern blots and determined the transcription pattern of DNA from the walk. We detect a single gene within the domain defined by breakpoint mapping. We conclude that we have identified the hunchback gene because three mutations that inactivate hb physically interrupt or delete this gene. Northern analysis shows that the hb gene gives rise to at least five overlapping transcripts ranging in length from 2.6 to 3.5 kilobases. S1 nuclease and primer extension experiments demonstrate that the gene employs two promoters and three polyadenylation sites. The two hb promoters have different temporal specificities. Transcripts arising from the upstream promoter are detected from 0-12 hours of embryogenesis as well as in adult female and male RNA preparations. Transcripts arising from the downstream promoter accumulate only from 0-6 hours of embryogenesis. During the syncytial blastoderm stage, transcripts from the hb gene accumulate over a broad anterior and a narrow posterior domain. This pattern sharpens during the late blastoderm/early gastrula stage to produce an embryo with two stripes of hybridization anterior and one stripe posterior. Later, hb transcripts are detected within the ventral hypoderm in extended germ band stage embryos.